Pentatricopeptide repeat protein MID1 modulates nad2 intron 1 splicing and Arabidopsis development - Peng Zhao (Nature Portfolio, 2020)
Abstract As one of the best-studied RNA binding proteins in plant, pentatricopeptide repeats (PPRs) protein are mainly targeted to mitochondria and/or chloroplasts for RNA processing to regulate the biogenesis and function of the organelles, but its molecular mechanism and role in development remain to be further revealed. Here, we identified a mitochondria-localized P-type small PPR protein, MITOCHONDRION-MEDIATED GROWTH DEFECT 1 (MID1) that is crucial for Arabidopsis development. Mutation in MID1 causes retarded embryo development and stunted plant growth with defects in cell expansion and proliferation. Molecular experiments showed that MID1 is required for the splicing of the nad2 intron 1 in mitochondria. Consistently, mid1 plants display significant reduction in the abundance and activity of mitochondrial respiration complex I, accompanied by abnormal mitochondrial morphology and energy metabolism. Furthermore, MID1 is associated with other trans-factors involved in NICOTINAMIDE ADENINE DINUCLEOTIDE HYDROGEN (NADH) DEHYDROGENASE SUBUNIT 2 (nad2) intron 1 splicing, and interacts directly with itself and MITOCHONDRIAL STABILITY FACTOR 1 (MTSF1). This suggests that MID1 most likely functions as a dimer for nad2 intron 1 splicing. Together, we characterized a novel PPR protein MID1 for nad2 intron 1 splicing.